Literary Connections and Problems of Literary Translation - Sharkova Alexandra Valeryevna (Genius Journals, 2022)
About literary connections and problems of literary translation, about the emergence of occasional words and the difficulties associated with the translation of English-language occasionalism’s.
Keywords: Translation; translation problems; occasionalism